Formulasi dan Uji Aktivitas Antibakteri Sediaan Spray Antiseptik Tangan Non Alkohol Infusa Daun Kemangi (Ocimum basilicum L.) dan Lidah Buaya (Aloe Vera (L.) Burm.f.) Terhadap Bakteri Staphylococcus aureus ATCC 25923 - Agustin, Eriska; Prasetyo, Dani; Azzahra, Nia; Muchtar, Muni’ah (JURNAL KESEHATAN TERAPAN, 2022)
The rapid spread of the Covid-19 virus has caused the WHO to declare the Covid-19 outbreak a global pandemic. However, public awareness of the importance of maintaining hand hygiene is still very low. The use of hand sanitizers is now increasingly widespread. Basil leaves and aloe vera have the potential to be developed as hand antiseptics because they contain secondary metabolites such as flavonoids, alkaloids, saponins and tannins. This study aims to formulate a non-alcoholic hand antiseptic spray preparation of basil and aloe vera infusion and whether it has antibacterial activity against Staphylococcus aureus ATCC 25923. Formulation of hand antiseptic spray preparation use various extract concentrations, namely F1 (20%), F2 (40%), F3 (60%), F4 (80%), and (F5 100%). Testing of antibacterial activity by agar diffusion method measuring the diameter of the inhibition zone of Staphylococcus aureus bacteria. From the results of the study, it was found that the five non-alcoholic hand antiseptic spray formulations infusion of basil and aloe vera leaves were in liquid form, had striking colors, had the same odor and were stabel for 14 days. The preparation looks homogeneous when applied to a glass object. The pH produced from this hand antiseptic spray preparation ranged from 4.5 to 6.5. The results of the antibacterial activity test showed that the inhibition of Staphylococcus aureus bacteria at F3 (60%) was 5.14 mm, F4 (80%) was 6.24 mm, and F5 (100%) was 7.26 mm which was classified as medium strength. Keywords: aloe vera, antiseptic spray, infusion, kemangi basil, Staphylococcus aureus